Investigations on the synthesis, characterization and electrochemical properties of [2FeNi] cluster complexes. (15th May 2021) - Mu, Chao; He, Jiao; Lü, Shuang; Yang, Jun; Xie, Ying; Hu, Kui; Yan, Peng; Li, Yu-Long
Graphical abstract: Four new [2FeNi] cluster complexes 1 –4 have been synthesized by reactions of nickel complexes [(Ph2 P)NP(S)Ph2 R)]NiCl2 and [2Fe2S] cluster complex Fe2 (CO)6 (SH)2 in the presence of Et3 N. Complexes 1 –4 have been determined by elemental analysis, IR, NMR, UV, TGA and X-ray single diffraction analysis. Moreover, 1 –4 were observed to be catalysts for H2 evolution in the presence of weak acid CH3 CO2 H under electrochemical conditions. Abstract: To better investigate the coordination chemistry of [2Fe2S] cluster complexes and nickel complexes with the ligand of monosulfide bis(diphenylphosphino)(N-R)amine, four [2FeNi] cluster complexes Fe2 (CO)6 (μ3 -S)2 [Ni(Ph2 PNP(S)Ph2 CH2 CH(CH3 )2 )] (1 ), Fe2 (CO)6 (μ3 -S)2 [Ni(Ph2 PNP(S)Ph2 (CH2 )3 CH3 )] (2 ), Fe2 (CO)6 (μ3 -S)2 [Ni(Ph2 PNP(S)Ph2 CH(CH3 )2 )] (3 ) and Fe2 (CO)6 (μ3 -S)2 [Ni(Ph2 PNP(S)Ph2 CH2 CH2 CH3 ] (4 ) have been synthesized by reactions of [(Ph2 P)NP(S)Ph2 R)]NiCl2 and [2Fe2S] cluster complex Fe2 (CO)6 (SH)2 . Complexes 1 –4 have been determined by elemental analysis, IR, NMR, UV, TGA and X-ray single diffraction analysis. In all the complexes, the iron atoms are approximately coordinated in a square-pyramidal geometry and each nickel atom is coordinated in a slightly distorted planar geometry by one P and three S atoms. Moreover, 1 –4 were observed to be catalysts for H2 evolution in the presence of weak acid CH3 CO2 H under electrochemical conditions.